2012
DOI: 10.1021/ma3017037
|View full text |Cite
|
Sign up to set email alerts
|

Ethynyl-Capped Hyperbranched Conjugated Polytriazole: Click Polymerization, Clickable Modification, and Aggregation-Enhanced Emission

Abstract: Cu(I)-catalyzed azide−alkyne click polymerization, developed based on the click reaction, has become a powerful tool for the construction of functional polytriazoles with linear and hyperbranched structures. This method has, however, rarely been used for the preparation of functional hyperbranched conjugated polytriazoles (hb-CPTA). In this paper, soluble ethynyl-capped hb-CPTA with weight-averaged molecular weight of 39 500 was synthesized in high yield (84.4%) by the Cu(I)-catalyzed azide−alkyne click polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 124 publications
1
54
0
Order By: Relevance
“…. Subsequently, this reaction has been exploited to a large extent in polymer chemistry for synthesizing linear polymers , hyperbranched copolymers , graft copolymers , block copolymers , and polymer‐composites .…”
Section: Introductionmentioning
confidence: 99%
“…. Subsequently, this reaction has been exploited to a large extent in polymer chemistry for synthesizing linear polymers , hyperbranched copolymers , graft copolymers , block copolymers , and polymer‐composites .…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate tetrakisalkynyl-substituted tetraphenylethylene 1 was readily synthesized in three steps from 4,4'-dibromobenzophenone according to the reported procedures. 12 The platinum-acetylide complex 2 was then prepared via the cross-coupling reaction of 1 with trans-PtI 2 (PMe 3 ) 2 catalyzed by CuI in a mixture solvent of THF and diethylamine at room temperature. Finally, the similar coupling reaction of the intermediate 2 with the terminal acetylene compound 3 bearing long alkyl chain resulted in the target complex TPA in high yield.…”
mentioning
confidence: 99%
“…S4, when the concentration of TPA was increased from 5.0 × 10 -4 to 8.0 × 10 -3 M, the resonance signals corresponding to the amide proton displayed a gradual downfield from δ = 7.62 to 7.67 ppm, which was indicative of the existence of hydrogen-bonding interactions during the formation of supramolecular aggregate in TPA. Moreover, it has been reported that fluoride anion (F -) can induce a deprotonation process of amide group, 12 thereby disturbing the hydrogen-bonding between amides. Therefore, the existence of hydrogen bonding interactions during the self-assembly process could be further supported by studying the stability of organometallic gel after the addition of F into the gel of TPA.…”
mentioning
confidence: 99%
“…A solution of 1 (0.070 g, 0.16 mmol) and 3 (0.34 g, 0.98 mmol) in diphenyl ether (8 mL) were added to a hydrothermal bomb and heated for 24 h in a 200 °C oven. Then the reaction mixture was cooled to room temperature, loaded into a column of silica gel, and the product was separated by using dichloromethane/hexane (1:9) as the eluent to obtain the desired product as a pale‐yellow solid (130 mg, 46 %).…”
Section: Methodsmentioning
confidence: 78%